Consumption and income inequality in the US since the 1960s - Bruce D. Meyer; James X. Sullivan (American Enterprise Institute (AEI), 2017)
Meyer and Sullivan examine income inequality between 1963 and 2014 using the Current Population Survey and consumption inequality between 1960 and 2014 using the Consumer Expenditure Survey.
Keywords: A; 330; Income inequality; consumption